Intelligent reflecting surface-enabled electromagnetic stealth for 6G: recent advances and future prospects - MA Tiantian; ZHENG Beixiong; XIONG Xue; ZHANG Rui (Dianxin kexue)
The rapid development of wireless technology has driven a high level of informatization in modern warfare, opening a new era in electronic countermeasures (ECM). With the continuous innovation of advanced radar technology, the survival capability of weapons and equipment such as missiles and aircraft is facing unprecedented challenges. The development and application of electromagnetic stealth technology can effectively enhance the survivability of modern weapons, which becomes a crucial direction for military technology development. However, traditional electromagnetic stealth technologies are often constrained by practical conditions and fail to meet the stealth requirements of military operations. To address this issue, intelligent reflecting surface (IRS)-enabled electromagnetic stealth technology was proposed. This technology utilized IRS to suppress or redirect reflected signals, thus achieving adaptive transparent or deceptive electromagnetic stealth. To fully explore the great potential of IRS in the field of electromagnetic stealth, the basic principles, system models, design challenges, and open issues of IRS-enabled electromagnetic stealth were discussed, aiming to provide directional guidance for the future development of electromagnetic stealth technology.